Clinical features of transverse myelitis associated with systemic lupus erythematosus. (April 2020) - Zhang, S; Wang, Z; Zhao, J; Wu, D i; Li, J; Wang, Q; Su, J; Xu, D; Wang, Y; Li, M; Zeng, X
Objective: This study aimed to identify the clinical characteristics and prognostic factors of systemic lupus erythematosus with transverse myelitis (SLE-TM) in a relatively large patient series. Methods: This retrospective study considered 45 SLE-TM individuals treated as inpatients and outpatients at Peking Union Medical College Hospital between 1993 and 2018. SLE-TM patients were compared with 180 controls, and SLE-TM patients with neuromyelitis optica spectrum disorder (NMOSD) were compared to those without NMOSD. Results: Compared to controls, the SLE-TM group frequently had a fever and had a significantly higher positive rate of anticardiolipin and lupus anticoagulant. Among the 45 patients, 22 met the NMOSD criteria. Compared to non-NMOSD patients, NMOSD patients had a lower incidence of rash ( p  = 0.023), serositis ( p  = 0.042) and renal disorder ( p  = 0.073); a lower prevalence of decreased complement ( p  = 0.083); and lower rates of positive anti-dsDNA ( p  = 0.074) and anti-Sm ( p  = 0.042). Among 22 SLE-TM patients with NMOSD, 18 underwent aquaporin 4 antibody testing, with 11 showing positive results. Out of the 45 patients, 39 were given methylprednisolone pulse treatment. After treatment, 32 patients had lower-limb muscle strength recovery (recovered group), whereas 13 had no change and persistent severe neurological deficits (non-recovered group). Compared to the recovered group, the non-recovered group were younger ( p  = 0.002), had a higher likelihood of having a fever ( p  = 0.020), initial severe myelitis ( p  < 0.001), long spinal segment involvement ( p  = 0.017) and higher C-reactive protein levels ( p  = 0.020). Methylprednisolone pulse given within two weeks of onset was more frequent in the recovered group than in the non-recovered group ( p  = 0.082). Conclusions: Disease characteristics differed between SLE-TM patients with and without NMOSD. SLE and NMOSD tended to be co-morbidities. Initial severe neurological impairment, extensive spinal cord lesions, hyper-inflammation and delayed steroid impulse treatment could be predictors of poor outcome for SLE-TM.